2022
DOI: 10.1186/s12890-022-02137-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymphocyte count for in-hospital mortality in patients with severe AECOPD

Abstract: Background Patients with severe acute exacerbations of chronic obstructive pulmonary disease often have a poor prognosis. Biomarkers can help clinicians personalize the assessment of different patients and mitigate mortality. The present study sought to determine if the lymphocyte count could act as a risk factor for mortality in individuals with severe AECOPD. Methods A retrospective study was carried out with 458 cases who had severe AECOPD. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
5
0
2
Order By: Relevance
“…This study revealed that lower lymphocyte level was also an independent risk factor for bacteremia. Previous studies have shown that low lymphocyte counts are associated with poor prognosis in acute and chronic inflammatory conditions such as sepsis, cancer, and cardiovascular and pulmonary diseases [22][23][24]. However, it has not yet fully understood how low lymphocyte causes immune system abnormalities in patients with pediatric UTI and increases bacteremia [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that lower lymphocyte level was also an independent risk factor for bacteremia. Previous studies have shown that low lymphocyte counts are associated with poor prognosis in acute and chronic inflammatory conditions such as sepsis, cancer, and cardiovascular and pulmonary diseases [22][23][24]. However, it has not yet fully understood how low lymphocyte causes immune system abnormalities in patients with pediatric UTI and increases bacteremia [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that hypoalbuminemia leads to oxidative stress with cellular damage and apoptosis. Together with albumin dosage, a low TC and lymphocyte count are also associated with higher mortality, reflecting a deterioration in nutritional status and a decreased immune and inflammatory status [ 26 , 27 ]. The CONUT score carried out at the moment of admission and represented a vicious cycle well; indeed, patients with multimorbidity tend to suffer malnutrition through many mechanisms, such as fluid retention, long bed stay, lack of appetite leading to inflammation, and neurohormonal activation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes were the only type of leukocytes with values outside the reference range; more precisely, below-normal levels (lymphopenia). Both leukocytosis and lymphopenia are often encountered during AECOPD episodes, when the immune response is activated due to an underlying infection or inflammation in the airways [ 32 , 33 , 34 , 35 ]. However, these immune responses alone are not specific to AECOPDs and can occur in response to various other infections and inflammatory conditions [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selection bias occurs when the adjustment fails to address systematic differences between the adjusted groups, leading to biased estimates [ 51 ]. Since all biochemical analyses were performed for patients during the exacerbation periods, it is also plausible that their CBC profiles and YKL-40 levels were more deranged vs. stable periods [ 35 , 39 ]. As a result, the magnitude of changes in these parameters may be higher and hence more relevant to understanding the immunopathological connection between YKL-40 and CBC in COPD.…”
Section: Discussionmentioning
confidence: 99%